Further study on carbon fixation using green power for a solar-assisted multi-generation system with carbon capture. (15th January 2023) - Qu, Wanjun; Gao, Yang; He, Song; Zhang, Jing; Peng, Kewen; Wu, Haifeng; Wang, Ruilin; Hong, Hui
Highlights: An approach to storing carbon dioxide is described for carbon-based energy systems. The abandoned renewable energy can be further reused to reduce CO2 emissions. Cascade utilization of energy improves the exergy efficiency of the system by 10% Nearly half of CO2 is stored without cutting down the performance of components. Exergy and energy efficiencies of methanol synthesis reach about advanced 76% and 56%. Abstract: For carbon-based thermal systems, a serious challenge to achieving carbon neutralization is carbon emission reduction. Currently, advanced chemical looping combustion can help thermal systems to realize carbon capture without energy consumption. This study further develops the carbon fixation process of thermal systems using green power. In detail, hydrogen generation and methanol synthesis units are integrated into a multi-generation system, which follows the principle of energy quality matching. Green power, solar heat, methane, high- and low-temperature heat, and mechanical work are reasonably utilized in hydrogen generation, preheating reactants, methanol synthesis, and purifying methanol. The case study shows that the proposed system's exergy efficiency is enhanced by 10 % compared with the reference system. In addition, about 43 % of carbon dioxide is stored in the form of methanol without cutting down the performance of system components. The energy and exergy efficiencies in the methanol synthesis are 56.36 % and 75.66 %, respectively, indicating the advantages of the proposed system over those proposed in extant research. In addition, these efficiencies are still higher than 50 % and 75 %, respectively, when the incident radiance is larger than 600 W/m 2 . This study also investigates the effect of electrolytic cell stack and incident irradiance on system performance. Results indicate that the proposed system can directly utilize fluctuating green power without using expensive batteries; moreover, the irreversibility of the multi-generation system is improved. These findings not only broaden the scope of application of green power but also allow to further realize the clean and efficient utilization of fossil fuels.